Impact of Anti-Corruption War on National Development in Nigeria - Tochukwu Nwachukwu, Stephen; Simon C. , Atigwe; AmaraOnwuka, Ifunanya; Kaycee Okeke, Ogochukwu (International Journal of Psychosocial Rehabilitation, 2021)
Nigeria has been severally described as a paradox judging from her enormous wealth and resources yet stuck in the shackles of underdevelopment. It was in the light of this disillusionment that the majority of Nigeria’s electorates voted out President Goodluck Jonathan and accepted General MuhammaduBuhari whose main campaign promise centered on a three-point agenda; fight against corruption, security and building the economy. There was widespread hope that the retired General would be courageous enough to tame corruption and unearth solutions to other problems confronting Nigeria. However, five years into his administration, issues of corruption, insecurity, and widespread poverty are still commonplace. Against this backdrop, this paper used a documentary research method to examine the impact of Buhari’s anti-corruption war on national development. It found out that notwithstanding the efforts of the government to salvage the menace of corruption, Nigeria according to the latest corruption index scored 26/100 which indicates she is more corrupt under the current administration than ever before. More so, indices of corruption are still pervading all nooks and crannies of Nigeria. Thus, reducing corruption to the barest minimum is the pathway to achieving sustainable development and unlocking the dividends of democratic governance in Nigeria. It, therefore, recommended the institutionalization of transparency and the use of ICT in government transactions.